2019
DOI: 10.1002/ecs2.2874
|View full text |Cite
|
Sign up to set email alerts
|

Location‐specific factors influence patterns and effects of subsistence sea otter harvest in Southeast Alaska

Abstract: To better understand the spatial context of population dynamics of sea otters (Enhydra lutris) in Southeast Alaska (SEAK), we investigated the spatial and temporal patterns of subsistence sea otter harvest and assessed the effect of harvest on population growth. U.S. federal law permits subsistence harvest of sea otters and sale of clothing and handicrafts made by coastal Alaska Natives. Hunters are required to self‐report these harvests along with information on date, location, age class, and sex. Using harve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 55 publications
(176 reference statements)
1
21
4
Order By: Relevance
“…We also found that sea otters additionally concentrate in areas where commercial fisheries are closed, as well as in protected areas, where subsistence harvest of sea otters is not permitted (i.e., Glacier Bay; Table 1), which suggests greater prey availability, foraging habitat, and mortality risk are strong drivers of sea otter distribution and abundance. Our finding that sea otters exhibit higher residence time closer to human communities is seemingly inconsistent with previous findings of exposure to subsistence hunting influencing sea otter movement (Hoyt, 2015) and population growth (Raymond et al, 2019). However, the diffusion model is likely capturing what happens during the initial colonization of areas closer to communities, and, in the longer-term, areas closer to communities where harvest is common may act as population sinks (Raymond et al, 2019).…”
Section: Spatial Variability In Abundancecontrasting
confidence: 95%
See 3 more Smart Citations
“…We also found that sea otters additionally concentrate in areas where commercial fisheries are closed, as well as in protected areas, where subsistence harvest of sea otters is not permitted (i.e., Glacier Bay; Table 1), which suggests greater prey availability, foraging habitat, and mortality risk are strong drivers of sea otter distribution and abundance. Our finding that sea otters exhibit higher residence time closer to human communities is seemingly inconsistent with previous findings of exposure to subsistence hunting influencing sea otter movement (Hoyt, 2015) and population growth (Raymond et al, 2019). However, the diffusion model is likely capturing what happens during the initial colonization of areas closer to communities, and, in the longer-term, areas closer to communities where harvest is common may act as population sinks (Raymond et al, 2019).…”
Section: Spatial Variability In Abundancecontrasting
confidence: 95%
“…Our finding that sea otters exhibit higher residence time closer to human communities is seemingly inconsistent with previous findings of exposure to subsistence hunting influencing sea otter movement (Hoyt, 2015) and population growth (Raymond et al, 2019). However, the diffusion model is likely capturing what happens during the initial colonization of areas closer to communities, and, in the longer-term, areas closer to communities where harvest is common may act as population sinks (Raymond et al, 2019).…”
Section: Spatial Variability In Abundancecontrasting
confidence: 95%
See 2 more Smart Citations
“…Recent studies of the sea otter population in Southeast Alaska used integrated data models to investigate regional population trends and density-dependent effects [ 19 ] and influence of subsistence harvest [ 22 ]. While the approaches applied in these studies accounted for movements between discrete sub-regions within Southeast Alaska (i.e., immigration and emigration), they assumed a known intrinsic growth rate and did not explicitly incorporate a mechanistic model of population spread that would naturally capture movements of recolonizing individuals throughout this continuous geographic area.…”
Section: Introductionmentioning
confidence: 99%